Breaking rules children in conflict with the law and the juvenile justice process. (Save the Children-UK, 2004)
Complete findings of three studies that looked into the profile of children in conflict with the law, and their situation and experiences in the justice administration process. The studies were conducted in the three main urban centers in the Philippines, namely, Metro Manila, Cebu City and Davao City. These studies also present specific cases, highlight emerging gaps and issues, and put forward recommendations for the five pillars of justice - the community, law enforcement, prosecution, the courts and correction - to address the needs and concerns, and promote the rights of children who come into conflict with the law. Includes summary and consolidation of the three researches.